2020
DOI: 10.1111/faf.12441
|View full text |Cite
|
Sign up to set email alerts
|

Are fishers poor? Getting to the bottom of marine fisheries income statistics

Abstract: Fishers' economic status is hard to assess because fisheries socio-economic data, including earnings, are often not centrally available, standardized or accessible in a form that allows scaled-up or comparative analyses. The lack of fishing income data impedes sound management and allows biased perceptions about fishers' status to persist. We compile data from intergovernmental and regional data sets, as well as case-studies, on income earned from marine wild-capture fisheries. We explore the level and distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
(57 reference statements)
1
19
0
Order By: Relevance
“…The GI values range from 0 (even distribution of income across fishers) to 1 (one fisher receives all income). There is some evidence to suggest that disparity in economic benefits may be relatively more pronounced within some fisheries compared to other sectors (Ferrol‐Schulte et al, 2014; Teh et al, 2020), which would make our assumption conservative, but this is difficult to discern given limited current research on the topic.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The GI values range from 0 (even distribution of income across fishers) to 1 (one fisher receives all income). There is some evidence to suggest that disparity in economic benefits may be relatively more pronounced within some fisheries compared to other sectors (Ferrol‐Schulte et al, 2014; Teh et al, 2020), which would make our assumption conservative, but this is difficult to discern given limited current research on the topic.…”
Section: Methodsmentioning
confidence: 98%
“…Around 230 million people benefit from fisheries, either directly from fishing (51 million) or indirectly through activities such as processing, packaging, trading and tourism services (179 million; Teh & Sumaila, 2013). However, fishing is often associated with poverty (Béné & Friend, 2011), and studies have demonstrated that even though fishers are certainly not always the “poorest of the poor” (Teh et al, 2020), fishers in at least a third of coastal nations live below their poverty line (Teh et al, 2020). Additionally, fisheries are also affected by ongoing global challenges, including climate change (Barange et al, 2018; Sumaila et al, 2011), pollution (Hughes et al, 2003), habitat degradation (Hughes et al, 2003), illegal activities (Rudd & Branch, 2016), over‐capacity (Pauly, 1990) and inequitable distribution of access to and benefits from resources (Cisneros‐Montemayor et al, 2019; Finkbeiner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Gendered division of labor can exist in fisheries, but Weeratunge et al (2010) argue that research should move beyond this limited perspective. Gender inequality in fisheries income is widely known (Zhao et al 2013, Teh et al 2020), yet the underlying causes are diverse. Compared to male fishers, women could be disadvantaged by being restricted to just gleaning, processing, and selling activities (Santos 2015, Furkon et al 2019, being restricted to intertidal areas (Siar 2003, de la Torre-Castro et al 2017, having poorer access to boats (Gerrard and Kleiber 2019), being given lower prices by traders (Purcell et al 2016), and even being excluded in some fisheries, thus obtaining less catch (Chapman 1987.…”
Section: Small-scale Fisheries Income and Well-beingmentioning
confidence: 99%
“…A main driver of catch rates and fishery income in Samoa was access to a boat. Across fisheries globally, boat owners tend to earn more than nonowners (Teh et al 2020). In some fisheries, women's limited access to fishing equipment restricts their access to certain fishing grounds and consequently reduces their catches and income (Fröcklin et al 2014).…”
Section: Fishing Income and Costsmentioning
confidence: 99%
See 1 more Smart Citation